(untitled) (Ciudades, 2017)
In France, the former urban model, characterised by centralism, state control, technocracy and authoritarianism takes a decisive turn since 1980. Decentralization rules voted in the 80´s, encouraged by left-wing Government, have enabled the substitution of state officials by local representatives in the decision-making process on regional and local urban actions. Since then, renewals, innovations and new concepts would appear. Nevertheless, during the last decades, the most impressive and expensive urban actions accomplished in France share the same features: socio-spatial polarization, which translates and materialises within the space the social logic of capitalism: unequal and combined development, as well as hierarchy of public spaces. In short, the relevant public authorities and private parties have profited these new developments, and citizens play a minimum role on these actions.